Work-related quality of life of psychologists in the single welfare system in eleven municipalities of the Bolsão Region in the State of Mato Grosso do Sul (Research, Society and Development, 2023)
Goal: analyze the main Quality of Life aspects by relating work to the experiences of Psychology professionals acting in public policies of the Bolsão region in the State of Mato Grosso do Sul, Brazil. Methodology: this was an epidemiological, descriptive, and cross-sectional study involving 54 psychologists. The Work-Related Quality of Life Scale was used to determine the participants’ Quality of Life at Work scores. For this purpose, the Chi-square test and Fisher's exact test (where applicable) were applied, establishing proportional differences regarding the domain among the groups. Result: female predominance in the profession; use of alcohol; fatigue during the day; struggle to stay focused at work, and labor violence. The study reveals that psychologists face challenges that negatively affect their Work-Related Quality of Life, including work overload, lack of emotional support, and a hard time balancing personal and professional life. Final considerations: it is necessary to implement attention and caring strategies aimed at improving Work-Related Quality of Life, such as: reviewing work organization methods in the causes of dissatisfaction and mental illness; fostering a healthy and balanced work environment; developing emotional support and mental health care programs; offering training and refresher courses; encouraging self-care, and establishing a balance between personal and professional lives.